2019
DOI: 10.1016/j.jcmgh.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The CCR2+ Macrophage Subset Promotes Pathogenic Angiogenesis for Tumor Vascularization in Fibrotic Livers

Abstract: Background & AimsHepatocellular carcinoma (HCC) typically arises in fibrotic or cirrhotic livers, which are characterized by pathogenic angiogenesis. Myeloid immune cells, specifically tumor-associated macrophages (TAMs), may represent potential novel therapeutic targets in HCC, complementing current ablative or immune therapies. However, the detailed functions of TAM subsets in hepatocarcinogenesis have remained obscure.MethodsTAM subsets were analyzed in-depth in human HCC samples and a combined fibrosis–HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 43 publications
0
77
1
1
Order By: Relevance
“…43 The angiogenic remodeling correlated with macrophage activation and was blocked by inhibiting cytokines for macrophage recruitment. Macrophages activation and the consequences on angiogenesis were described by Bartneck et al 44 recently. Activated macrophages secrete growth factors such as bFGF, TGF-α, IGF-I, PDGF, VEGF, TGF-β, and cytokines such as IL-1, IL-6, IL-8, and TNF-α, which promote matrix remodeling and modulate the migration and proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…43 The angiogenic remodeling correlated with macrophage activation and was blocked by inhibiting cytokines for macrophage recruitment. Macrophages activation and the consequences on angiogenesis were described by Bartneck et al 44 recently. Activated macrophages secrete growth factors such as bFGF, TGF-α, IGF-I, PDGF, VEGF, TGF-β, and cytokines such as IL-1, IL-6, IL-8, and TNF-α, which promote matrix remodeling and modulate the migration and proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…(60) Additionally, cell sorting from mice subjected to a combined fibrosis-cancer model induced by diethylnitrosamine followed by repetitive CCl 4 injections revealed distinct coexisting MoMF populations with specific gene expression patterns, suggesting inflammatory capacity (immature myeloid infiltrate), angiogenic and fibrogenic activity (classical tumorassociated macrophages), or immune-suppressive functions (myeloid-derived suppressor cells). (86) While KCs are stationary and crucial for initiating inflammation, drastic changes occur in the MoMF compartment following injury. MoMFs have been shown to be recruited to the injury site just a few hours after acute injury (40,53,87) and account for the majority of hepatic macrophages in models of chronic liver injury.…”
Section: Kupffer Cells and Monocytes: The Sentinels And The Emergencymentioning
confidence: 99%
“…As such, CCL2 expression has a prognostic value in patients with hepatocellular carcinoma, and CCR2 blockade has been shown to inhibit cancer growth by favoring an antitumoral immune response (136) and inhibiting angiogenesis. (86) Recently, CD163, a macrophage-specific marker with anti-inflammatory functions, has been used to evidence the presence of tumor-associated macrophages in cholangiocarcinoma. The authors concluded that CD163 + macrophage number correlated with cholangiocarcinoma stage.…”
Section: Prognostic Value Of Macrophage-related Markers In Human Livementioning
confidence: 99%
“…The drug is a Spiegelmer® ( l ‐isomers of RNA oligonucleotides)‐based therapeutic agent that interacts specifically with MCP‐1 and inhibits its activity . Very recently, the drug showed preclinical success in the treatment of liver cancer . Bindarit is a small‐molecule inhibitor of MCP‐1 that has completed phase II clinical trials for the treatment of diabetic nephropathy.…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 99%